County-level Correlates of Human Trafficking Arrest Levels in Ohio: social Disorganization, Social Capital, and Physical Contexts - Benanzer, Hillary (Crime & delinquency, 2023)
The present study investigated county-level correlates of human trafficking arrest levels in Ohio. Study variables were comprised of measures derived from social disorganization, social capital, and physical contexts of Ohio counties (N = 88). A negative binomial regression analysis was conducted to examine the relationship between county arrest counts and independent variables. Larger counts of human trafficking arrests were explained by higher levels of racial/ethnic heterogeneity, a social disorganization measure. Additionally, an increase in demand reduction strategy use was associated with a predicted increase in human trafficking arrest count. Further research on the influence of social variables and anti-human trafficking efforts on human trafficking arrest levels is needed to better understand how to effectively identify and combat human trafficking.